Alternative discourses in the coaching of high performance youth sport: exploring language of sustainability - Grahn, K. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
This paper focuses on discourses of coaching in high performance sports. Through three interviews with a youth swimming coach, I explore ways of constructing coaching practice. I examine coaching as an educational practice and use discourse analysis as an analytic framework. The notion of interpretative repertoires is employed as a specific theoretical concept to consider the linguistic resources that the coach draws upon. The results suggest that a variety of resources exist to make sense of coaching. Interpretative repertoires promoting alternative views of performance (i.e. not simply winning), as well as sustainable repertoires that emphasize well-being, learning for life and an equitable coach-athlete relationship, may provide alternative ways of thinking about coaching elite youth sports.